Hierarchically nanostructured MnO2 electrodes for pseudocapacitor application. Issue 104 (31st October 2016) - Ryu, Ilhwan; Kim, Green; Yoon, Hajin; Ahn, Sang Jung; Yim, Sanggyu
Abstract : The supercapacitive properties of hierarchically nanostructured manganese oxide (MnO2 ) electrodes were investigated. Abstract : The supercapacitive properties of hierarchically nanostructured manganese oxide (MnO2 ) electrodes were investigated. The hierarchical MnO2 nanostructures consisting of nanowires in a small length scale and inverse-opal nanostructures in a large length scale were successfully fabricated using a combination of colloidal nanosphere lithography and cyclic voltammetric deposition. A maximum specific capacitance, C sp, of 714 F g −1 at the scan rate of 10 mV s −1 was obtained, which was significantly larger than 556 F g −1 observed for the MnO2 electrode with simple nanowire structures. The enhancement of the C sp value is attributed to the lower charge-transfer and diffusive resistance of the hierarchical nanostructures, which was estimated by electrochemical impedance measurements. The other capacitive properties were also improved considerably. The C sp retention for the hierarchical nanostructure electrode after 5000 charge–discharge cycles was 75.4%, and the voltammetric response at high scan rates was 1.8 times larger than that for the simple nanowire electrode.